EMPOWERMENT LEADERSHIP AND PERFORMANCE: ANTECEDENTS - Larasati Ahluwalia (Universitas Teknokrat Indonesia, 2020)
The development of research on empowerment leadership has continued to increase over the last few decades. However, an in-depth discussion of the antecedents of empowerment leadership is still limited. This study explores several antecedents of empowerment leadership, including collectivism and narcissism orientation. In addition, the inconsistency of the influence of empowerment leadership on the performance of subordinates was still found in several studies. The results of this study indicate that collectivism and narcissism orientation have an influence on leadership empowerment. The results of this study support the influence of empowerment leadership on the performance of subordinates.